Improving the Students’ Speaking Skill Through Snakes and Ladders (Sl) on Second Semester Students of English Study Program at Stain Bengkalis - Rini Fitria; Ervina Ervina (Universitas Muhammadiyah Tangerang, 2020)
The aim of the research was to describe the learning atmosphere during the implementation of “Snakes and Ladders” in teaching Speaking. Besides, the research was also designed to know how the improvement of the students’ Speaking skill during the implementation of “Snakes and Ladders”. This research was a classroom action research. The participants of this research were 27 second semester students of English Study Program at STAIN Bengkalis. This research was conducted in two cycles by following the procedure of action research, i.e. planning, implementing, observing, and reflecting. In collecting the data, the researcher used observation, questionnaire, and test. The lecturer was the researcher assisted by collaborator as observer. The questionnaire was given to the students before and after the implementation of “Snakes and Ladders”. The tests were in the form of pre-test, post-test 1 and post-test 2. The data were analyzed qualitatively and quantitatively. The qualitative data were analyzed using Interactive Model of Data Analysis as propounded by Matthew M. Miles and A.M. Huberman. The results of the research showed that the learning atmosphere also improved. The class became more active and confident. Furthermore, “Snakes and Ladders” was able to improve the students’ Speaking Skill. It was proven by the increase of the students’ mean score from 41.16 in pre-test to 46.21 in cycle 1, and 48.98 in cycle 2, although the results of the research were just a little bit improvement. It could be concluded that the use of “Snakes and Ladders” has proven to be an effective way in teaching-learning of Speaking Skill on Second Semester of English Study Program at STAIN Bengkalis.